2023
DOI: 10.1111/nph.19085
|View full text |Cite
|
Sign up to set email alerts
|

Inner bark vs sapwood is the main driver of nitrogen and phosphorus allocation in stems and roots across three tropical woody plant communities

Julieta A. Rosell,
Carmen R. Marcati,
Mark E. Olson
et al.

Abstract: Summary Nutrient allocation is central to understanding plant ecological strategies and forest roles in biogeochemical cycles. Thought to be mainly driven by environmental conditions, nutrient allocation to woody organs, especially to living tissues, is poorly understood. To examine the role of differences in living tissues (sapwood, SW, vs inner bark, IB), organs, ecological strategies, and environmental conditions in driving nutrient allocation and scaling in woody plants, we quantified nitrogen and phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 94 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…To determine the concentration of NO 3 -N and PO 4 3 -P in roots and leaves, each plant was cut and divided into roots, stems, and leaves; subsequently, these were dried in an oven at 100 ± 5 • C for 4 h. Once the vegetative parts were dry, each part was ground in a mortar and then passed through a 40-mesh mesh [37,38]. The powder obtained was stored in polyethylene bags for the determination of nitrate and phosphate concentrations.…”
Section: Phytoaccumulation Evaluationmentioning
confidence: 99%
“…To determine the concentration of NO 3 -N and PO 4 3 -P in roots and leaves, each plant was cut and divided into roots, stems, and leaves; subsequently, these were dried in an oven at 100 ± 5 • C for 4 h. Once the vegetative parts were dry, each part was ground in a mortar and then passed through a 40-mesh mesh [37,38]. The powder obtained was stored in polyethylene bags for the determination of nitrate and phosphate concentrations.…”
Section: Phytoaccumulation Evaluationmentioning
confidence: 99%
“…Previous research has shown that reducing leaf litter inputs can increase soil bulk density with possible detrimental consequences for soil fertility (Sayer, 2006), suggesting that the impacts of CWD removal on soil bulk density and fertility are worth examining. Recent studies also offer evidence that the wood of tropical trees constitutes a significant reservoir of rock-derived (i.e., originally mobilized by rock weathering) nutrients such as phosphorus (P), potassium (K), magnesium (Mg), and calcium (Ca), in addition to nitrogen (Bauters et al, 2022;Heineman et al, 2016;Inagawa et al, 2023;Rosell et al, 2023). This suggests that CWD removal could also affect soil fertility in tropical forests by curtailing the recycling of key nutrients from vegetation to soil.…”
Section: Introductionmentioning
confidence: 99%